Insertion of sustainable strategic design in the furnishings of micro and small enterprises - Braga, Juliana Cardoso; Da Silva, Fernando Moreira; Ferrão, Leonor; Paschoarelli, Luis Carlos [UNESP] (Common Ground Research Networks, 2017)
There are around thirteen thousand, five hundred micro and small enterprises (MSEs) acting in the furniture sector in Brazil, whose production is essentially made to order. The manufacturing processes are not sustainable, resulting in large volumes of waste discarded in a wasteful manner on the outskirts of the cities, composed, mainly, of the remains of reconstituted wood (sawdust and debris from artificial laminates and MDF). The spacing of MSEs in the sector extends over a vast territory, and the reduced dimension of these productive structures has been causing difficulties for united action calling for a change in the productive paradigm, in that these small organizations are, on the whole, too preoccupied with their own subsistence. Therefore, this article intends to present alternatives in sustainable strategic design, with the objective of minimizing the waste produced by these companies, promoting transformations in society. In methodological terms, active research will be used, since it favors the exploration and analysis of the set of interactions occurring during the process, and it allows for a reflexive action with the goal of reaching improvements in results. It is expected that this work, will result in the minimization of the environmental impact created by the furniture manufacturer MSEs, reducing the generation of waste for part of the sector.
Keywords: Ecodesign; Environmental Labeling; Furniture Manufacturer MSEs; Social Design; Sustainability